Inclusivity and Diversity in Global Creative Industries: A Narrative Review - Cendekia, Damas (Harmonia : Journal of Music and Arts, 2025)
The global creative industries are undergoing a critical transformation as inclusivity and diversity emerge as central imperatives shaping cultural sustainability and innovation. This narrative review synthesizes literature from 2000 to 2024 to examine inclusivity in the arts across four key domains: representation in artistic content, accessibility of cultural spaces, culturally responsive pedagogy, and structural-economic frameworks. Literature was collected through comprehensive searches in Scopus, Web of Science, and Google Scholar, using targeted keywords such as “inclusivity in arts,” “diversity in creative industries,” and “representation in cultural production.” Studies meeting inclusion criteria provided empirical data, theoretical frameworks, and case studies relevant to inclusivity. Findings indicate that inclusive representation in visual arts, film, and digital media enhances belonging and social inclusion, while accessibility initiatives such as universal design and sensory-friendly adaptations improve participation for marginalized groups. Culturally responsive pedagogies foster empathy and reduce prejudice, situating education as a powerful site for social transformation. Structural and economic analyses reveal that policy reforms and equitable funding are essential to dismantling systemic barriers, with comparative perspectives illustrating varying successes across global regions. Despite promising initiatives, gaps remain regarding the sustainability and systemic impact of inclusivity efforts, particularly in underexplored regions and long-term evaluations. This review underscores the urgency of structural reform and highlights the need for collaborative, context-sensitive strategies to foster inclusivity. Future research should investigate the effectiveness of digital platforms in supporting underrepresented voices while ensuring equitable resource distribution. By addressing these challenges, creative industries can be redefined as equitable spaces that reflect and nurture the diversity of the societies they serve.